Potassium and Yttrium Complexes of a Rigid Bis‐Phosphido POP‐Donor Ligand. Issue 22 (14th June 2017) - Motolko, Kelly S. A.; Emslie, David J. H.; Jenkins, Hilary A.; Britten, James F.
Abstract : Dilithiation of 4, 5‐dibromo‐2, 7‐di‐ tert ‐butyl‐9, 9‐dimethyl‐xanthene (XBr2 ) followed by addition of 2 equiv. of (2, 4, 6‐triisopropylphenyl)dichlorophosphine (TrippPCl2 ) afforded 4, 5‐bis[(2, 4, 6‐triisopropylphenyl)chlorophosphino]‐2, 7‐di‐ tert ‐butyl‐9, 9‐dimethylxanthene (XP2 Cl2 ), which was reduced to 4, 5‐bis[(2, 4, 6‐triisopropylphenyl)phosphino]‐2, 7‐di‐ tert ‐butyl‐9, 9‐dimethylxanthene (H2 XP2 ) using excess LiAlH4 . Deprotonation of H2 XP2 with excess KH in DME provided the dipotassium salt, [K2 (XP2 )(dme) n ] (1 ; n = 2.5–4), and stirring1 in THF followed by recrystallization from hexanes yielded tetrametallic [K4 (XP2 )2 (THF)4 ] (2 ) which features a central K4 P4 cage. Reaction of [YI3 (THF)3.5 ] with [K2 XP2 (dme)2.5 ] afforded a mixture of products including [(XP2 )YI(THF)2 ] (3 ) and (PTripp)3 ; pure3 could be isolated in low yield by extraction with a minimum volume of hexanes or O(SiMe3 )2 . In the solid state, 3 adopts a face‐capped trigonal bipyramidal coordination geometry with a planar xanthene backbone and an angle of 85° between the P(1)/C(4)/C(5)/P(2) and P(1)/Y/P(2) planes. Abstract : A rigid bis‐phosphido POP‐donor ligand was synthesized and complexed with potassium and yttrium. This yielded a unique example of a cubic K4 (PR2 )4 cage and a bonding mode to yttrium that differs significantly from that of the bis‐amido analogue.